Public management and governance - Bovaird, A. G.; Löffler, Elke (London, UK : New York, USA: Routledge, Taylor & Francis Group, 2024)
"Public Management and Governance is the leading text in international public management and governance and an ideal introduction to all aspects of this field. It combines rigorous insight from pre-eminent scholars around the world with supportive, thoughtful, and intuitive structure and pedagogy. This revised and updated fourth edition responds to the significant changes in the external environment, as well as the field itself. It includes six new chapters covering aspects of increasing importance: Public management and governance developments in non-OECD countries Risk and resilience Innovation in public management and governance Digital public management Digital public governance Behavioural approaches to public policy Throughout the new edition, there is a wealth of new content on emergent topics such as collaborative leadership, diversity, equity, complexity theory and evidence-informed policy. Each chapter is supplemented with discussion questions, group and individual exercises, case studies and recommendations on further reading; this edition also includes more international cases. This highly respected text is an essential resource for all students on undergraduate and postgraduate courses in public management, public administration, government, and public policy as well as for policymakers and practitioners seeking an up-to-date guide to the field"--
Includes bibliographical references and index.
Keywords: Public administration; Government productivity; Legitimacy of governments; Public administration -- Citizen participation